2000
DOI: 10.1111/j.1530-0277.2000.tb01972.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Moderate and High Doses of Alcohol on Attention, Impulsivity, Discriminability, and Response Bias in Immediate and Delayed Memory Task Performance

Abstract: These results clearly demonstrated a time-course effect of the 1.0 g/kg alcohol dose on attention, impulsivity, discrimination, and response criteria when a variety of dependent measures are used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(50 citation statements)
references
References 47 publications
3
46
0
1
Order By: Relevance
“…The observed impact of drinking on impulsivity may be reflective of the effect of rash behavior occurring while intoxicated on an individual's subsequent ratings of his or her typical personality. This would be consistent with the findings of previous studies where, when administered alcohol, social drinkers tended to behave impulsively on subsequent laboratory tasks (Dougherty et al, 2000(Dougherty et al, , 2008, and research indicating that heavy drinkers demonstrate an increase in impulsive behavior following a high dose of alcohol that light drinkers do not (Reed et al, 2012). Considering specifically the bidirectional relation of alcohol use and urgency, individuals high in the trait may find that, because of peer acceptance of heavy drinking, consuming alcohol is an acceptable way to act out while experiencing strong affect, and intoxication may in turn contribute to increases in intense emotion and impulsive behavior.…”
Section: Discussionsupporting
confidence: 92%
“…The observed impact of drinking on impulsivity may be reflective of the effect of rash behavior occurring while intoxicated on an individual's subsequent ratings of his or her typical personality. This would be consistent with the findings of previous studies where, when administered alcohol, social drinkers tended to behave impulsively on subsequent laboratory tasks (Dougherty et al, 2000(Dougherty et al, , 2008, and research indicating that heavy drinkers demonstrate an increase in impulsive behavior following a high dose of alcohol that light drinkers do not (Reed et al, 2012). Considering specifically the bidirectional relation of alcohol use and urgency, individuals high in the trait may find that, because of peer acceptance of heavy drinking, consuming alcohol is an acceptable way to act out while experiencing strong affect, and intoxication may in turn contribute to increases in intense emotion and impulsive behavior.…”
Section: Discussionsupporting
confidence: 92%
“…It is possible that the variation in results is due to experimental methodologies; however, it is also possible that alcohol affects various cognitive functions differently. While the present research focused on the effects of alcohol on a memory and recall task, how alcohol precisely impacted the various functions [14] required to acquire and store information such as stimulus detection, perception or encoding remains unknown and is hence an area for future research.…”
Section: Limitations and Future Researchmentioning
confidence: 98%
“…This index is based on a widely used and accepted substance -alcohol, where its effect on cognition and human performance is widely documented. [13][14][15][16][17][18] However, the effect of alcohol on performance is not always in a dose dependent relationship. For example, Moskowitz and Depry [33] found that while alcohol degraded performance in a divided attention task, it failed to negatively impact performance on a vigilance task.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Impulsivity was assessed by The Immediate and Delayed Memory Task (IMT/DMT 2.0) (Dougherty & Marsh, 2003; Dougherty, Marsh, & Mathias, 2002; Dougherty, Marsh, Moeller, Chokshi, & Rosen, 2000) . The IMT/DMT has demonstrated validity as a measure of impulsivity for individuals with psychiatric disorders.…”
Section: Methodsmentioning
confidence: 99%